Enhancing quality of prosthetic services with process and outcome information. (April 2017) - Heinemann, Allen W; Ehrlich-Jones, Linda; Connelly, Lauri; Semik, Patrick; Fatone, Stefania
Background: Prosthetic clinics in the United States must attain accreditation in order to receive reimbursement from Medicare. The accreditation process requires clinics to establish and implement performance management plans and quality improvement activities. This report describes the experience of seven prosthetic clinics in collecting patient-reported outcome data and using it to improve quality of services. Objectives: To describe the experience of prosthetic clinics implementing outcome monitoring and quality improvement activities as part of routine patient care. Study design: Qualitative, ethnographic design. Methods: Clinics incorporated the Orthotics Prosthetics Users' Survey into routine care for patients aged 18 years and older who received a new lower limb prosthesis or socket. Orthotics Prosthetics Users' Survey measures lower extremity functional status, quality of life, and satisfaction with device and services. Clinics selected Orthotics Prosthetics Users' Survey-derived indicators on which to implement quality improvement action plans. Results: Seven clinics participated, but only three were able to sustain data collection. Two clinics initiated quality improvement activities focused on improving declining satisfaction or functional scores. Conclusions: Quality improvement activities based on patient-reported outcomes require a high degree of organizational commitment and support. External facilitation can support clinics' quality improvement activities. Clinical relevance: This project illustrates the challenges of sustaining quality improvement activities using patient-reported outcome data in prosthetic clinics.